2015
DOI: 10.4155/bio.15.61
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Highly Sophisticated Flow Cytometry Assays in Multicenter Clinical Studies: Considerations and Guidance

Abstract: Flow cytometry is increasingly becoming an important technology for biomarkers used in drug discovery and development. Within clinical development flow cytometry is used for the determination of PD biomarkers, disease or efficacy biomarkers or patient stratification biomarkers. Significant differences exist between flow cytometry methodology and other widely used technologies measuring soluble biomarkers including ligand binding and mass spectrometry. These differences include the very heavy reliance on aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…For the TVT, its utility has already been described in this fashion in publications such as Poirier et al (9) and Sommer et al (14). Regression analysis results showed that there was only one case where the correlation coefficient (r value) failed to meet the ≥0.90 target (TVT vs BD = 0.89 for CD16/56 on Day 11) for both devices.…”
Section: While There Have Been Comparative Studies Between the Transfmentioning
confidence: 80%
See 1 more Smart Citation
“…For the TVT, its utility has already been described in this fashion in publications such as Poirier et al (9) and Sommer et al (14). Regression analysis results showed that there was only one case where the correlation coefficient (r value) failed to meet the ≥0.90 target (TVT vs BD = 0.89 for CD16/56 on Day 11) for both devices.…”
Section: While There Have Been Comparative Studies Between the Transfmentioning
confidence: 80%
“…These results highlight that both devices can be used in a capacity where a centralized analysis laboratory for immunophenotyping is required for clinical development purposes. For the TVT, its utility has already been described in this fashion in publications such as Poirier et al (9) and Sommer et al (14).…”
Section: While There Have Been Comparative Studies Between the Transfmentioning
confidence: 99%
“…Several variables such as sample/specimen choice and preparation, instruments setup and alignment, and data acquisition and analysis impact the outcome and reliability of large scale multicenter studies involving FCM; as identified by the survey and the live discussions. The main outcomes and suggestions from the WS were: Control of sample stability (from few hours to several days) is a critical factor in choosing a distributed processing approach and several methods to enhance sample stability are well documented and should be consulted . Lab‐to‐lab variations in sample processing and analyses were considered major sources of data variability resulting from subjective analyses along with the potential variability introduced by the use of multiple instruments and operators. The need for access to disease‐state samples for use in assay development and as control material. Suitable samples could come from commercial vendors, clinical partner networks, or the creation of biobanks of disease samples. …”
Section: Discussionmentioning
confidence: 99%
“…• Control of sample stability (from few hours to several days) is a critical factor in choosing a distributed processing approach and several methods to enhance sample stability are well documented and should be consulted (93,94). • Lab-to-lab variations in sample processing and analyses were considered major sources of data variability resulting from subjective analyses along with the potential variability introduced by the use of multiple instruments and operators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation